2021
DOI: 10.5194/isprs-archives-xliii-b3-2021-155-2021
|View full text |Cite
|
Sign up to set email alerts
|

Land Subsidence Hazard in Iran Revealed by Country-Scale Analysis of Sentinel-1 Insar

Abstract: Abstract. Many areas across Iran are subject to land subsidence, a sign of exceeding stress due to the over-extraction of groundwater during the past decades. This paper uses a huge dataset of Sentinel-1, acquired since 2014 in 66 image frames of 250 × 250 km, to identify and monitor land subsidence across Iran. Using a two-step time series analysis, we first identify subsidence zones at a medium scale of 100 m across the country. For the first time, our results provide a comprehensive nationwide map of subsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The vertical InSAR velocity for Iran contains a large number of subsidence signals associated with groundwater extraction (Haghshenas Haghighi & Motagh, 2021), with diameters of <10 km to >100 km and peak rates of >100 mm/yr. Most subsidence signals show seasonal variation in the cumulative displacement series correlated with seasonal variations in rainfall (Modarres & Sarhadi, 2009), with a significant variation in the strength of the seasonal term between basins.…”
Section: Iranian Velocity Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical InSAR velocity for Iran contains a large number of subsidence signals associated with groundwater extraction (Haghshenas Haghighi & Motagh, 2021), with diameters of <10 km to >100 km and peak rates of >100 mm/yr. Most subsidence signals show seasonal variation in the cumulative displacement series correlated with seasonal variations in rainfall (Modarres & Sarhadi, 2009), with a significant variation in the strength of the seasonal term between basins.…”
Section: Iranian Velocity Fieldmentioning
confidence: 99%
“…Interferometric Synthetic Aperture Radar (InSAR) time‐series analysis is a well‐established technique for measuring ground deformation at the level of millimeters per year (Morishita et al., 2020), with spatial resolutions in the tens of meters, providing spatially continuous observations over hundreds of kilometres that are useful for regional continental tectonic studies (Elliott et al., 2016). Iran has been the focus of numerous InSAR‐based studies over the past 20 years, capturing deformation from groundwater extraction (Babaee et al., 2020; Ghorbani et al., 2022; Haghshenas Haghighi & Motagh, 2021; Motagh et al., 2017), active salt diaprism (Barnhart & Lohman, 2012; Roosta et al., 2019), and co‐ and postseismic deformation (Liu et al., 2021; Penney et al., 2015; Plattner et al., 2022). Regarding interseismic strain accumulation, a common target of InSAR analysis due to the small magnitude of the signal and the implications for seismic hazard, previous Iran InSAR studies have focused on individual fault structures such as the Main Kopet Dagh Fault (Dodds et al., 2022; Walters et al, 2013), the Main Recent Fault (Watson et al., 2022), the North Tabriz Fault (Aghajany et al., 2017; Karimzadeh et al., 2013; Rizza et al., 2013), and the Doruneh Fault (Pezzo et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One such study analyzed a 3-year period of Sentinel-1 data between 2014 and 2017 to identify hot spots of subsidence across the country. The findings revealed widespread land subsidence, with rates of up to 30 cm/year in certain areas (16). Other studies integrated InSAR data into machine learning models to upscale the measurements and predict land subsidence at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…The SBAS-InSAR technique with Sentinel-1 data has been widely used to estimate surface displacement 7 , 24 – 33 . For example, Haghshenas Haghighi and Motagh 30 studied the land subsidence hazard in Iran by country-scale analysis of sentinel-1 InSAR data through the years of 2014 to 2017. In their study, the subsidence zones were observed to be highly correlated with agricultural areas.…”
Section: Introductionmentioning
confidence: 99%